2009
DOI: 10.1177/070674370905401103
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Prevalence and Treatment of Bipolar Disorder among Immigrants: Results from an Epidemiologic Survey

Abstract: Objective: To add to the limited data on the prevalence, clinical characteristics, and treatment of bipolar disorder (BD) among immigrants. Method: Data were obtained from a large epidemiologic survey, the Canadian Community Health Survey-Mental Health and Well-Being (CCHS 1.2). Lifetime prevalence rates of BD were compared between immigrant and nonimmigrant respondents. Among BD subjects (n = 831), sociodemographic, clinical, and mental health treatment use variables were compared based on immigrant status. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 65 publications
(85 reference statements)
2
9
1
Order By: Relevance
“…This observation is consistent with data from the CCHS, which shows lower risk of mental illness among migrants. [16][17][18][19] However, it is inconsistent with international data on migrants' mental health, which shows higher risk among migrants, though these results may not be generalizable to Canada per se. 4,15 Our analyses revealed that participants who had recently migrated to Canada, within 5 years, had better mental health scores than those who had migrated to Canada more than 10 years before.…”
Section: Migration and Mental Healthcontrasting
confidence: 44%
See 1 more Smart Citation
“…This observation is consistent with data from the CCHS, which shows lower risk of mental illness among migrants. [16][17][18][19] However, it is inconsistent with international data on migrants' mental health, which shows higher risk among migrants, though these results may not be generalizable to Canada per se. 4,15 Our analyses revealed that participants who had recently migrated to Canada, within 5 years, had better mental health scores than those who had migrated to Canada more than 10 years before.…”
Section: Migration and Mental Healthcontrasting
confidence: 44%
“…Findings from the Canadian Community Health Survey (CCHS) point to lower rates of psychiatric disorders, including unipolar and bipolar disorders, among first-generation migrants compared with Canadian-born residents. [16][17][18][19] However, results from regional studies do not always concur with those from the CCHS. 20,21 For example, some studies in specific Canadian cities report greater incidence rates of mental health disorders among migrant populations.…”
mentioning
confidence: 44%
“…Accordingly, hospital admission for affective disorders may be less common among immigrant groups. 28,39 Consistent with this notion, Schaffer et al 64 found that in Canada immigrants were less likely than members of the host population to use outpatient mental health services for affective disorders.…”
Section: Discussionsupporting
confidence: 56%
“…A number of studies have reported more hallucinations in ethnic minorities with psychotic disorders (Harvey et al 1990;Arnold et al 2004;Kennedy et al 2004), and in a literature review childhood abuse was found to be a causal factor in the development of psychosis and schizophrenia, more specifically hallucinations and particularly voices commenting and command hallucinations (Kapur, 2003). We suggest that this could partially explain the reasons why several studies have found a skewed distribution of psychosis diagnosis, with patients from ethnic minorities receiving more schizophrenia diagnoses and less bipolar disorder diagnoses than patients from the majority population (Schaffer et al 2009;Gara et al 2012). This first-rank symptom is considered sufficient to meet the A criterion of characteristic symptoms of schizophrenia in DSM-IV (APA, 1994).…”
Section: Discussionmentioning
confidence: 70%